The A & P Case: A Study in Applied Economic Theory - Adelman, M. A. (Quarterly Journal of Economics, 1949)
Introduction, 238. — I. Selling Policy, 239. — II. Integration, 244. — III. Buying Policy, 247. — IV. Conclusions, 255.